The Impact of Country of Origin on Brand Equity: An Analysis of The Wine Sector - Nadia Passagem; Catia Fernandes Crespo; Nuno Almeida (Wine Economics and Policy)
The purpose of this study is to explore the country of origin´s effects on brand equity dimensions. This research selected wine as the product category and data were collected from Portuguese and Canadian consumers. Our conceptual framework incorporates the influence of country of origin on brand equity dimensions, composed by brand loyalty, brand associations, brand awareness and perceived quality, as well as the brand equity subsequent effect on purchase intention. The hypotheses were tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results of the Portuguese sample indicate that the country of origin affects positively all the brand equity dimensions. The Canadian sample results show that country of origin affects brand loyalty and perceived quality, but there is no significant effect on brand associations and brand awareness dimensions.